PROSES PEMBENTUKAN ADJEKTIVA DALAM BAHASA MINANGKABAU DI KECAMATAN NANGGALO KOTA PADANG - Putri, Dina Amrianti Andika; Agustina, Agustina (Jurnal Bahasa dan Sastra, 2019)
This study aims to describe the process of adjective formation in the Minangkabau language in Nanggalo Subdistrict, Padang City. This type of research is qualitative research using descriptive methods. The data of this study are the adjectives used by the people in Nanggalo Subdistrict, Padang City. The methods and techniques of data collection are carried out through two stages simultaneously, namely the smak method and proficient methods with detailed description techniques. The technique of analyzing data is done by identifying and classifying data based on groups, namely the process of forming adjectives. Based on the results of research and discussion, conclusions can be drawn as follows. The process of forming Minangkabau language adjectives in Nanggalo Subdistrict, Padang City is as follows: (1) affixed namely (a) prefix, (b) confix, and (c) combination of affixes, (2) duplicated namely (a) repeating all (dwilinga) and (b) confix R + infix, reset all + an, (3) compound namely (a) coordinative and (b) sub-coordinative, and (4) combined prefixes namely (a) A + R and (b) R + A.Keywords: Adjectives, Word-forming, Minangkabau Language